Simplified finite-element modelling for tunnelling-induced settlements - Suched Likitlersuang; Chanaton Surarak; Suchatvee Suwansawat; Dariusz Wanatowski; Erwin Oh; Arumugam Balasubramaniam (My University, 2014)
Tunnelling-induced ground surface settlement prediction still adopts empirical and analytical approaches; thus a step further in using a practical numerical analysis is now a challenging task. Because the deformation during tunnelling is a three-dimensional problem, several features were incorporated in two-dimensional analyses to capture aspects that are important in governing behaviour in the missing third dimension. This paper aims to present simplified methods for ground settlement computation of tunnelling works using the PLAXIS finite-element programme. Three simplified methods – contraction ratio, stress reduction and modified grout pressure – were considered in this study. Practical application requires correlations among these three methods. Such correlations among the three methods are proposed in this study and can be used in geotechnical practice. The results were based on a series of finite-element analyses of the Blue Line Bangkok Mass Rapid Transit tunnels. The geotechnical parameters were selected based on soil investigation reports carried out for construction purposes. The soil constitutive model adopted herein was the hardening soil model on soft and stiff clays. All the finite-element simulations were compared with the measured field deformations. Therefore, the analysis results can be considered as a Class-C prediction (back-analysis).
Keywords: Settlement (finance); Hardening (computing); Geotechnical Engineering and Analysis